2017
DOI: 10.1186/s13052-017-0423-3
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine as an effective intervention to improve antibiotic appropriateness prescription and to reduce costs in pediatrics

Abstract: Implementation of antimicrobial stewardship program is a pivotal practice element for healthcare institution. We developed a remote infectious disease consultancy program via telemedicine in a high-specialized pediatric cardiac hospital. A consultation for antibiotic strategy for each patient was available via telemedicine in addition to biweekly discussion of all clinical cases. Aim of this study was to evaluate the impact of the remote stewardship program in terms of a) appropriateness of antibiotic prescrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…Thirty-nine (39/113, 34.5%) were multicentre studies: 43.6% (17/39) were set in the USA, 35.9% (14/39) in Europe, and the rest 20.5% in Asia and Africa (8/39). [52,58,66,67,72,106,112,115,124,137,141] as an outcome used mostly to analyse audit and feedback ASP [58,67,74,141]. In five cases, no changes were reported [58,66,74,106,115], while the other seven studies showed an increased susceptibility of the bacteria analysed [52,67,72,112,124,137,141].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-nine (39/113, 34.5%) were multicentre studies: 43.6% (17/39) were set in the USA, 35.9% (14/39) in Europe, and the rest 20.5% in Asia and Africa (8/39). [52,58,66,67,72,106,112,115,124,137,141] as an outcome used mostly to analyse audit and feedback ASP [58,67,74,141]. In five cases, no changes were reported [58,66,74,106,115], while the other seven studies showed an increased susceptibility of the bacteria analysed [52,67,72,112,124,137,141].…”
Section: Resultsmentioning
confidence: 99%
“…[52,58,66,67,72,106,112,115,124,137,141] as an outcome used mostly to analyse audit and feedback ASP [58,67,74,141]. In five cases, no changes were reported [58,66,74,106,115], while the other seven studies showed an increased susceptibility of the bacteria analysed [52,67,72,112,124,137,141]. The most interesting results were a decrease in extended spectrum beta-lactamase (ESBL) producers E. coli and K. pneumoniae [72,112,124]; a reduction in the rate of P. aeruginosa carbapenem resistance subsequent to an observed reduction in the rate of antimicrobial days of therapy (DOT) [67,124]; and, in two studies set in outpatient setting, an increase in erythromycin-sensitive S. pyogenes following a reduction in the use of macrolides [137,141].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Moreover, 4 reports have described tele-consultation interventions that used secure videoconference technology to bring individuals from remote locations together for regularly scheduled, multidisciplinary team meetings. [10][11][12][13] An additional publication describes an on-demand approach in which providers requested advice from an on-call infectious disease expert and received real-time feedback over the telephone and through the electronic medical record. 14 Of these 8 programs, 5 detailed quantifiable decreases in the use of antibiotics and prevalence of multidrugresistant pathogens or Clostridiodes difficile.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Synchronous programs used technology to permit a multidisciplinary team of professionals to discuss cases in real time and also allowed for consultation to occur outside of scheduled sessions. [15][16][17][18] In addition to infectious disease physicians and pharmacists, team members included epidemiologists, microbiologists, administrators, information technology specialists, infection control staff members, as well as other physicians. To help broaden the inclusion of antimicrobial stewardship principles across clinical disciplines, the VAST specifically involved staff nurses.…”
Section: Discussionmentioning
confidence: 99%